Longevity interventions temporally scale healthspan in Caenorhabditis elegans - Cyril Statzer; Peter Reichert; Jürg Dual; Collin Y. Ewald (iScience, 2022)
Summary: Human centenarians and longevity mutants of model organisms show lower incidence rates of late-life morbidities than the average population. However, whether longevity is caused by a compression of the portion of life spent in a state of morbidity, i.e., “sickspan,” is highly debated even in isogenic Caenorhabditis elegans. Here, we developed a microfluidic device that employs acoustophoretic force fields to quantify the maximum muscle strength and dynamic power in aging C. elegans. Together with different biomarkers for healthspan, we found a stochastic onset of morbidity, starting with a decline in dynamic muscle power and structural integrity, culminating in frailty. Surprisingly, we did not observe a compression of sickspan in longevity mutants but instead observed a temporal scaling of healthspan. Given the conservation of these longevity interventions, this raises the question of whether the healthspan of mammalian longevity interventions is also temporally scaled.